FEATURES OF THE DEVELOPMENT OF THE RUSSIAN FRONTIER IN THE NORTH CAUCASUS - Magaramov, Sarafutdin Arifovic (History, Archeology and Ethnography of the Caucasus, 2023)
In recent decades, both foreign and Russian historiography have increasingly focused on the concept of the frontier when examining the formation of various territories within the Russian state, including the North Caucasus. The utilization of the frontier concept for studying Russian-Caucasian relations is now widely accepted in historiography, eliminating one-sided assessments. The frontier theory serves as a fundamental concept, enabling the exploration of the complex dynamics between the peoples of the Caucasus and the Russian Empire from the standpoint of imperial power and mountain societies. Consequently, the frontier concept is integrated into the research methodology. This work aims to investigate the essence and distinctive features characterizing the development of the Russian frontier in the North Caucasus. Unlike other Russian frontiers situated on various peripheries of the state, the North Caucasus frontier exhibits unique characteristics, notwithstanding the continuity of the Russian state as one of the actors. The identified features of the North Caucasian frontier – international, political, economic, and social – set it apart from similar phenomena along other geographical borders of the country, rendering it uniquely original. A key and distinctive aspect of the North Caucasus borderland was the coexistence, alongside the Russian frontier, of two additional Muslim frontiers – those of the Shah’s Persia and the Ottoman Empire, the latter predating the Russian one. This historical phenomenon is referred to as “polyfrontism” in historiography. The expansion of the Russian frontier in the North Caucasus consequently led to the gradual reduction and ultimately the abolition of Muslim frontiers. Nevertheless, remnants of the regional powers’ frontiers persist in the Caucasus in the present era. The “closure” of the Russian frontier in the North Caucasus transpired in the 1860s with the culmination of the Caucasian War and the definitive subjugation of the mountaineers by the Russian Empire. The considered features of the Caucasian frontier are not exhaustive and may be subject to further examinations.